2000
DOI: 10.1021/la000818y
|View full text |Cite
|
Sign up to set email alerts
|

Force Measurements between Bacteria and Poly(ethylene glycol)-Coated Surfaces

Abstract: The atomic force microscope (AFM) was used to directly measure the forces of interaction between E. coli D21 bacteria and hydrophilic glass or hydrophobic N-octadecyltrichlorosilane (OTS)-treated glass substrates coated with the block copolymers, poly(ethylene glycol) (PEG)-lysine dendron or Pluronic F127 surfactant, respectively. Short-range repulsive interactions between bacterial cells and substrates coated with the block copolymers were detected by the AFM over distances of separation comparable to the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 22 publications
5
117
0
Order By: Relevance
“…However, PEO with a molar mass of 3500 Da rendered the surface resistant to staphylococcal adhesion. Another study showed that surfaces with PEO chains with a molecular mass of 4500 and 20 000 Da blocked the adhesion of E. coli D 21 (Razatos et al, 2000). Surprisingly, it has also been found that a selfassembled monolayer of PEO with only six PEO units is able to prevent the adhesion of Sta.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, PEO with a molar mass of 3500 Da rendered the surface resistant to staphylococcal adhesion. Another study showed that surfaces with PEO chains with a molecular mass of 4500 and 20 000 Da blocked the adhesion of E. coli D 21 (Razatos et al, 2000). Surprisingly, it has also been found that a selfassembled monolayer of PEO with only six PEO units is able to prevent the adhesion of Sta.…”
Section: Discussionmentioning
confidence: 99%
“…Therewith, a PEO-brush forms a steric barrier preventing close approach and thus attenuates the attractive Lifshitz-Van der Waals interaction between the protein and the surface. PEO-coatings have also been investigated for their ability to prevent bacterial adhesion (Park et al, 1998;Razatos et al, 2000;Ista et al, 1996;Bridgett et al, 1992). Varying results have been obtained, ranging from reductions in bacterial adhesion of 98 % (Razatos et al, 2000;Ista et al 1996), 90-98 % (Bridgett et al, 1992) and between 0 and 90 % (Park et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First attempts in this direction were made by Razatos et al [980] who demonstrated that it is possible to coat silicon nitride AFM cantilevers including the tip with a layer of E. coli cells, if the cells were fixed by glutaraldehyde treatment. The authors took advantage of such functionalized tips to study the adhesion of E. coli [386,981] (see also Ref. [982]).…”
Section: Cell Probe Measurementsmentioning
confidence: 99%
“…A similar study has been done using AFM to find relation between surface charge heterogeneity and the deposition rates of colloids during their transport in porous media (Shellenberger and Logan, 2002). AFM has been used to understand the role polysaccharides present on bacterial cells play by offering steric hindrance and blocking the long range attractive forces between bacteria and substrata (Razatos et al, 2000).…”
Section: Principles Of Afmmentioning
confidence: 99%